Environmental Personhood - Gordon, Gwendolyn J. (Columbia Journal of Environmental Law, 2019)
Parks are people too, my friend. So quipped an August 2016 headline making reference at once to Mitt Romney’s flip commentary on corporations and to recent developments in New Zealand law enabling landscapes to be named as legal persons—that is, as entities possessing juridical rights akin to those of corporations. In the wake of this and other developments of the concept, legal personhood has struck observers as a promising tool for protecting nature—an idea overdue given the now seemingly unexceptional nature of corporate personhood in protecting corporate rights. Far from being the settled, stolid doctrine that its long tenure might have it appear to be, however, corporate personhood is quicksilver; it seems an endlessly adaptable concept. How might we come to understand the environment as a similarly flexible rights-holder in a way that is robustly protective of environmental interests? This Article argues that, as an example of how we came to see a non-human entity as a rights holder, corporate personhood may be a useful tool in moving toward understanding the environment as a rights holder. Legal personhood is not binary; it is not a yes-or-no proposition. The differentiation of legal rights and responsibilities starts, not ends, at the question of whether something may or may not be considered a person in the meaning of a statute. The real issue here is what, given the legal personhood of corporations or the environment, that means for how much that legal, practical, rhetorical entity—that category-for-legal-convenience—should be allowed to claim the rights of other shades of personhood. There is, after all, no such thing as a plain-old person; it is law that defines the categories of persons. The development of a concept of corporate personhood in American law was anything but inevitable. Although we are familiar now with “the idea of a corporation having ‘its’ own rights, and being a ‘person’ and ‘citizen’ for so many statutory and constitutional purposes,” the idea was perhaps as unsettling to contemporary jurists as that of environmental personhood might sound today. Just as “[t]hroughout legal history, each successive extension of rights to some new entity has been . . . a bit unthinkable,” so too does their contingency become practically unthinkable after they are normalized. Before environmental personhood becomes unremarkable, and thus unremarked-upon, we would do well to consider some of the contingencies in the development of the personhood concept as applied to corporations. Even among the very few jurisdictions that have developed concepts of environmental personhood, conceptions of that “personhood” are diverse. In 2014, Te Urewera, formerly a New Zealand national park, was declared to be a legal entity. The act making this designation transformed the land from government-owned national park to freehold land owned by itself. The country’s Whanganui River followed suit in 2017. Years prior to the movement in New Zealand law, Ecuador proclaimed under its constitution the rights of nature “to exist, persist, maintain and regenerate its vital cycles.” Nature here, instead of being named as a legal person directly, instead is given these rights by analogy to “persons and people.” In Bolivia, nature is defined as a juridical entity that “takes on the character of collective public interest.” In the United States, a number of local governing bodies promulgated ordinances recognizing the rights of nature. These new global legal developments arrive alongside what appears to be a wholesale re-evaluation of the place of human interests in relation to nature. New Zealand’s Te Urewera Act in particular is seen to be novel for its changes to the very nature of property ownership. It is an unequivocal rejection of a human-centered rights regime for protecting nature as property. In the end, our capacity to imagine a politics capable of encompassing things and places far outside of human lives or business interests has more to do with how well legal personhood will protect the environment than does any particular deployment of legal arguments for environmental personhood—just as has been the case in the development of the doctrine of corporate personhood in American law. To show why this is so, the Article is arranged as follows. Part II describes recent advances made in the concept of environmental personhood in locations as varied as Bolivia, Ecuador, India, and New Zealand. Part III examines the usefulness of corporate personhood doctrine as an analogy for proponents of the protection of the environment by means of the concept of personhood. Part IV examines the terms of the debate in more detail, considering the development of rights of nature arguments and the stakes of ontological claims regarding divisions between nature and people. Part V considers the significance of holistic theories of environmental protection to discourses of personhood. Finally, the Article offers some conclusions regarding the development of environmental personhood. Legal personhood may come to be as protective for environmental interests as it has been for corporate interests; it can become so by referencing the latter’s protean, politically fluid nature.